The moral economy of security. (November 2014) - Loader, Ian; Goold, Benjamin; Thumala, Angélica
In this article we draw upon our recent research into security consumption to answer two questions: first, under what conditions do people experience the buying and selling of security goods and services as morally troubling? Second, what are the theoretical implications of understanding private security as, in certain respects, tainted trade? We begin by drawing on two bodies of work on morality and markets (one found in political theory, the other in cultural sociology) in order to develop what we call a moral economy of security. We then use this theoretical resource to conduct an anatomy of the modes of ambivalence and unease that the trade in security generates. Three categories organize the analysis: blocked exchange; corrosive exchange; and intangible exchange. In conclusion, we briefly spell out the wider significance of our claim that the buying and selling of security is a morally charged and contested practice of governance.